New Approach for Refined Efficiency Estimation of Air Exchange Organization - Dovhaliuk, Volodymyr; Mileikovskyi, Viktor; ., . (International Journal of Engineering and Technology, 2018)
In the modern conditions, energy efficiency is one of the most important world problems. One of the important factors influencing the overall energy efficiency of buildings is air distribution in rooms. Literature review shows different options of efficiency estimation of air exchange with significant limitations. Some of them have non-obvious physical meaning. Certain of them do not take into account possible room zoning. Consideration of turbulence intensity in the efficiency estimation was not found. In this work, we propose an approach to estimate the air exchange efficiency in different kind of rooms. It is a relation of minimum room demands and inlet air potentials. Additional definitions are introduced for the parameters and demands estimation. The mechanical energy of the air is used for the estimation, which includes the energy of averaged motion and turbulent pulsation. Special approach is offered for turbulence intensity computation for energy calculations. The example of efficiency estimation of air exchange in a museum room with constant air volume system of air conditioning is solved.Â Â